Paul Ricœur: Hermeneia: Racconto dell’esperienza ed esperienza del racconto - Aversa, Luigi (B@belonline, 2021)
The essay points out the fundamental relationship between the philosopher Paul Ricœur and the psychoanalytic theory, highlighting how the experiential datum is a central point of the ‘depth psychology’ as well as of philosophy. Hermeneia, it is not only a linguistic interpretation but, with its explanatory function, ‘revealing’, it re-reveals, over a long time, the experience, which in addition to being lived is also told. This time, the narrative time, where everything deserves to be told, is where the psychoanalytic experience and Paul Ricœur philosophical experience meet.